PENGUKURAN KINERJA PDAM KOTA MAKASSAR BERBASIS BALANCED SCORECARD - Moh. Rafid Marwal; M. Wahyuddin Abdullah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This study aims to analyze the performance ratings of PDAM Makassar City based on performance assessment issued by BPPSPAM to assess the aspects studied in the form of managerial functions by using Balanced Scorecard approach as a measuring instrument. The research approach used is normative approach and using qualitative method. The results showed that the performance of financial perspective on the level of ability to meet short-term liabilities (cash ratio) companies experiencing illiquid where PDAM Makassar City is financial distress short-term. Customer perspective shows the result of customer growth ratio and domestic water consumption show less performance value. For internal business process perspective experiencing the same thing that waterlessness indicator happened big enough water loss, also because by error of recording (human error) related to record water account, this cause low water sold. While the perspective of human resources on the indicator ratio training and employee training load showed a degree that is not good, this case show development of employee competency is not top priority of PDAM Makassar City.Finally, although there are many problems found, but overall by looking at the accumulation value of balanced scorecard performance measurement of PDAM Makassar city shows a healthy performance (shows 3,37 points in 2015 and 3,39 points in 2014 , with the standard value of healthy performance category is ≥ 2,8 points).Researchers expect PDAM Makassar City to make improvements to the problems found, to create more optimal performance in the future.